Strategy and Opportunity for The Development of Duck Breeding Farm - L Hardy Prasetyo (Indonesian Center for Animal Research and Development, 2006)
The recent development of duck farming requires the availability of good quality breeding stocks commercially in order to improve productivity and efficiency . Presently, there is no commercial duck breeding farm which can produce good quality breeding stocks . This article presents information on alternatives in developing duck breeding farm, particularly for layer ducks . There are two alternative approaches in duck breeding farms : (1) Group breeding farm, which belongs to duck farmers' group, as part of a group production system, and (2) Commercial breeding farm, by an individual private company/Semi-Government Institution in a commercial scale and particularly for export market . A good breeding farm requires appropriate systems for selection and mating of the animals in order to guarantee the quality of the breeding stocks being produced . A breeding farm must be economically and technically feasible as an economic entity, so that economic analysis and marketing must be prepared seriously . Key words: Duck, model, breeding farm